Popped rice with distinct nutraceutical properties - Itagi, Hameeda; Sartagoda, Kristel June D.; Pratap, Vipin; Roy, Priyabrata; Tiozon, Rhowell N.; Regina, Ahmed; Sreenivasulu, Nese (Elsevier, 2023)
Iron-pan roasting is a common processing technique used in India to produce value-added popped rice. For the first time, traditional landrace genotypes black rice (Chak-hao), red (CRVR 68), Kalanamak, and a high-yielding variety Samba Mahsuri (SM) were extensively examined for the effects of the popping process on their physical and biochemical properties. SM had the highest volume increase and popping percentage, both of which are consumer-preferred attributes for popped products. The Fe content was significantly increased by popping in all genotypes. The Mg content of de-husked Red and Chak-hao did not substantially differ from that of its popped forms. Total starch decreased in popped red and Chak-hao, owing to amylose/amylopectin leaching from the grains. Popped landrace accessions retained most bioactives (∼70%, oryzanol, 14–28% total phenolic content, 48–65% total flavonoid content, and 38% total anthocyanin content) and antioxidant potency, especially in pigmented rice. Interestingly, the popped rice retained total dietary fibre across all genotypes. This work demonstrated that pigmented rice landraces can be transformed into nutraceutically-rich and wholesome, ready-to-eat popped rice product that is consumed as a primary product or as an ingredient to novel functional foods that could optimize human health.